Assessment of Foot Deformities in Patient with Knee Osteoarthritis - Musaid, Ruba (Al-Khwarizmi Engineering Journal, 2024)
Foot morphology evaluation techniques are commonly used to evaluate foot abnormalities. The foot is essential for keeping the biomechanical performance of the lower extremities. Knee osteoarthritis is a pathological condition that could lead to foot deformities. The major goal of this study was to investigate the prevalence of foot deformity in patients with Knee osteoarthritis. Another goal was to quantify the impact of pain and the severity of osteoarthritis foot morphological changes in Knee osteoarthritis patients.A total of seventy-eight participants took part in this study, including forty-six non-pathological subjects and thirty-two subjects diagnosed with knee osteoarthritis. Foot characteristics were assessed by a podoscope that can automatically estimate foot morphological parameters including Arch Index, Chippaux-Smirak Index, Staheli Index, Weisflog's index, Clarke’s angle and Hallux valgus angle. Numerous foot-related variables have been connected in a direct manner to knee osteoarthritis. Particularly, those who had knee osteoarthritis had substantially higher values for the Arch index (0.29±0.018; P=0.00), Chippaux-Smirak index (0.55±0.5; P=0.00), Staheli index (0.77±0.7; P=0.00), and Weisflog's index (2.7±0.25; P=0.00) than those who did not have this disease. Furthermore, their Clarke's angle and Hallux valgus angle exhibited high values of (30.27±2.7) and (13±1.8), respectively. There were also significant correlations found within the knee osteoarthritis group. There was, for example, a substantial positive correlation between the Arch Index and the Chippaux-Smirak Index (0.767; p=0.00), the Arch Index and the Staheli Index (r=0.35; p=0.04), and the Chippaux-Smirak Index and the Staheli Index (r=0.44; p=0.01). In terms of foot abnormalities, the Midfoot (333.528.6; p=0.00) was more significant than the Rearfoot (604.25±31.2; p=0.85) and Hindfoot (433.3±35.2; p=1.66). With association values of (r=0.4; p=0.02) and (r=0.4; p=0.04), the Arch Index and Chippaux-Smirak Index were both significantly linked with the severity of knee osteoarthritis.Foot abnormalities are substantially more prevalent in persons with Knee osteoarthritis. Collapsed medial longitudinal arch, transverse arch, and hallux valgus are all variables to consider in the management of Knee osteoarthritis. Healthcare providers may target Knee osteoarthritis effects on midfoot morphology with focused therapies. Custom orthotic devices, footwear adjustments, and particular workouts may enhance midfoot stability and alignment. Assessing foot morphology allows healthcare providers to enhance knee osteoarthritis therapy and patient results.